2011
DOI: 10.1080/02755947.2011.603651
|View full text |Cite
|
Sign up to set email alerts
|

Information Flow within the Social Network Structure of a Joint Strategic Plan for Management of Great Lakes Fisheries

Abstract: Transboundary fish stocks are governed by multiple entities, involving individuals with different expertise and sociocultural backgrounds and representing various institutions and jurisdictions. At times, individuals from these entities collaboratively make fishery governance decisions, and the existence of collegial or personal relationships may facilitate the decision‐making process and result in better management of fish stocks. Although studies have assessed several aspects of fisheries institutional struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…organizations. To our knowledge, this is the first study looking at information sharing in an Australian fishery social network and one of the few network studies looking at information sharing between small-scale fishery stakeholders globally (Bodin and Norberg, 2005;Leonard et al, 2011;Turner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…organizations. To our knowledge, this is the first study looking at information sharing in an Australian fishery social network and one of the few network studies looking at information sharing between small-scale fishery stakeholders globally (Bodin and Norberg, 2005;Leonard et al, 2011;Turner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of stakeholders in the management process (i.e., co-management), along with the study of social networks is fundamental when assessing fishery management approaches. One way to integrate the study of social networks in fisheries research is by better understanding informationsharing within the network and how the structure of the network influences this exchange (Leonard et al, 2011). Information exchange often depends on making and maintaining positive interactions with key individuals and organizations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Leonard et al . () found that a well‐integrated social network supported the effectiveness of a Joint Strategic Plan for Management of Great Lakes Fisheries. Participants in the Joint Strategic Plan formed strong social ties, benefitted from an easy exchange of information and their ability to share resources facilitated the implementation of the Plan.…”
Section: Factors That Influence Fisheries Management Decisionsmentioning
confidence: 95%
“…The emphasis on the importance of these meetings is a unique feature of the GLFC and GLATOS and has been identified for its success in promoting social ties and establishing relationships. These meetings are thought to increase the effectiveness of management coordination in the multi-jurisdictional Great Lakes (Leonard et al 2011). Although the Joint Strategic Plan and coordination efforts from the GLFC have been viewed as an important and successful initiative for improving coordination and communication among management jurisdictions and researchers, room for improvement still exists to bridge across differences in culture and norms of science and practice.…”
Section: The Science-practice Culture Divide Persistshow Can It Be Ovmentioning
confidence: 99%